The descent of love : Darwin and the theory of sexual selection in American fiction, 1871-1926 - Bender, Bert (University of Pennsylvania Press, 1996)
Upon its publication in 1871, Charles Darwin's The Descent of Man and Selection in Relation to Sex sent shock waves through the scientific community and the public at large. In an original and persuasive study, Bert Bender demonstrates that it is this treatise, rather than any of Darwin's earlier works, that provoked the most immediate and vigorous response from American fiction writers.